The Things You Can See Only When You Slow Down - Haemin Sunim; Chi-Young Kim and Haemin Sunim (London, UK. Penguin Books, 2017)
A renowned Buddhist meditation teacher, born in Korea and educated in the United States, illuminates a path to inner peace and balance amid the overwhelming demands of everyday life by offering guideposts to well-being and happiness in eight areas
Keywords: Conduct of life; Spiritual life